Scenario planning development for a furniture manufacturing company: the case of pt. Indo creative mebel - Djunaidi, Edi; P. K. Bintoro, Bambang (The Indonesian Journal of Business Administration, 2016)
Abstract --- Todayâ€™s furniture industry is changing fast and becoming more complex. Macro environment factors such as politics, economic, socio-cultural and technology have impact to the industry and yet difficult to predict. These uncertainties increase when a company move away from the present along the time. This study is intended to develop a set of business scenario for PT. Indo Creative Mebel (ICM), a private-owned furniture manufacturing company using scenario planning approach, in order to be able to response and adapt quickly with the future changes. This study identifies and analyzes its business issues and driving forces that have most impact and highest uncertainty degree. Two critical uncertainties identified in this study results in four plausible scenarios for the company. The narratives for each scenario are then created, with the implications and options that should be executed under each scenario. Furthermore, an early warning signals developed that serves as a watch-and-respond system or radar that could indicates what scenario that might be unfold. Hence, the company could be mentally prepared, better in strategic decision making and aligning its business strategy.Â Keywords: Scenario planning, furniture industry, business strategy, strategic planning